ANALISIS STRUKTUR FUNGSIONAL MODEL A.J GREIMAS DALAM LEGENDA LANTING MIHING - NFN Kambang (Balai Bahasa Kalimantan Tengah, 2017)
This study examines the Functional structure of Model A.J Greimas In Legends Lanting Mihing. The legend of Lanting Mihing is a folklore from the Kahayan river basin. This legend revolves around the courage of the central figure gained the expertise of how to make Lanting Mihing. The purpose of this writing is to know the structure in the legend story of Lanting Mihing the method in this writing is a qualitative method. To reveal the courage of this central figure then use functional structure theory proposed by A. J. Greimas. The results of Legend Lanting Mihing research led to a central figure named Bowak, there are 4 backgrounds in Legend Lanting Mihing ie background place, time, social, and psychology. Mandate delivered so that the younger generations do not forget the traditions that have been made by the ancestors, one of which way of making Lanting Mihing.